2014
DOI: 10.3329/birdem.v4i1.18546
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic Evaluation of the Tuboperitoneal Factors in Infertility

Abstract: Introduction:Infertility is defined as the inability of a couple to conceive with one year regular unprotected intercourses. 1 The prevalence of women diagnosed with infertility is approximately 13% with a range from 7-28% 2 in world wide.About 25% of cases of infertility are attributed to male factors. In female infertility, untreated infection, anovulation and endometriosis are major causes. Tubal and peritoneal factors are responsible for 30% to 40% cases of female infertility.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…Endometriosis was found in 4 (12.5%) cases with primary infertility and 2 (11.1%) cases with secondary infertility [14]. A similar study by Khan MI in Bangladesh in a study of 50 infertile patients, has shown pelvic pathology like endometriosis was present in 5(10%) cases ,adhesion was detected in 14(28%) and chocolate cyst was found in 3 (6%) cases [20]. In another similar study, Shetty SK et al showed endometriosis in 12(24%) cases and peritubal adhesion in 4(8%) cases where endometriosis was higher but adhesion was lower than our study [21].…”
Section: Resultsmentioning
confidence: 92%
“…Endometriosis was found in 4 (12.5%) cases with primary infertility and 2 (11.1%) cases with secondary infertility [14]. A similar study by Khan MI in Bangladesh in a study of 50 infertile patients, has shown pelvic pathology like endometriosis was present in 5(10%) cases ,adhesion was detected in 14(28%) and chocolate cyst was found in 3 (6%) cases [20]. In another similar study, Shetty SK et al showed endometriosis in 12(24%) cases and peritubal adhesion in 4(8%) cases where endometriosis was higher but adhesion was lower than our study [21].…”
Section: Resultsmentioning
confidence: 92%